Essential Genes of Vibrio anguillarum and Other Vibrio spp. Guide the Development of New Drugs and Vaccines - Bekaert, Michaël; Goffin, Nikki; McMillan, Stuart; Desbois, Andrew P. (Frontiers in Microbiology, 2021)
Essential genes in bacterial pathogens are potential drug targets and vaccine candidates because disrupting their function is lethal. The development of new antibiotics, in addition to effective prevention measures such as vaccination, contributes to addressing the global problem of bacterial antibiotic resistance. The aim of this present study was to determine the essential genes of Vibrio anguillarum, a bacterial pathogen of aquatic animals, as a means to identify putative targets for novel drugs and to assist the prioritisation of potential vaccine candidates. Essential genes were characterised by a Tn-seq approach using the TnSC189 mariner transposon to construct a library of 52,662 insertion mutants. In total, 329 essential genes were identified, with 34.7% found within the core genome of this species; each of these genes represents a strong potential drug target. Seven essential gene products were predicted to reside in the cell membrane or be released extracellularly, thus serving as putative vaccine candidates. Comparison to essential gene data from five other studies of Vibrio species revealed 13 proteins to be conserved across the studies, while 25 genes were specific to V. anguillarum and not found to be essential in the other Vibrio spp. This study provides new information on the essential genes of Vibrio species and the methodology may be applied to other pathogens to guide the development of new drugs and vaccines, which will assist efforts to counter antibiotic resistance.